An assay for proteinases and their inhibitors based on DNA/ethidium bromide fluorescence - Severini, Alberto; Richard Morgan, A. (Analytical biochemistry, 1991)
Proteinases and their inhibitors have become the subject of intense research interest recently, since they control a multitude of very important biological processes, from the development of λ phage to hypertension in humans. We have developed a simple and sensitive assay for detecting the activity of proteinases and of their proteinase inhibitors. The assay is based on ethidium bromide fluorescence, according to the following principles: (i) Ethidium bromide increases its fluorescence by 25-fold when it intercalates between base pairs of double-stranded DNA. (ii) Histones prevent this large increase in fluorescence by binding with high affinity to DNA thus blocking ethidium bromide intercalation. (iii) A proteinase that digests histones will make more DNA available for ethidium bromide intercalation, thereby producing an increase of fluorescence. Proteinase activity can easily be determined, in the presence of a DNA/histone complex, from the rate of ethidium fluorescence increase. In contrast, activity of a proteinase inhibitor is quantitated by the inhibition of fluorescence gain in the presence of a known amount of proteinase. This assay is rapid, simple, inexpensive, and, at the same time, accurate and sensitive enough to allow quantitation of nanogram amounts of various broad-specificity proteinases and their inhibitors. We show some possible applications of the assay (i) in testing column fractions during protein purifications, (ii) quantitation of α 1-antitrypsin in human serum, and (iii) detection of proteinase activity in cell extracts.